Continuance intention of IT professionals to telecommute post pandemic: A modified expectation confirmation model perspective - Lilian Anthonysamy (Knowledge Management & E-Learning: An International Journal, 2022)
This study investigates employees’ intentions to telecommute post-pandemic based on IT employees’ present work experiences. Perceived utility, contentment, and confirmation of expectations are proposed as factors of continuing intention to telecommute, according to the expectation-confirmation theory. The integration of work-life balance into the expectation confirmation theory was investigated to see if work-life balance influences employees’ continued intention to telecommute. Data from 131 Malaysian IT workers was used to test the hypothesised model. The findings backed up the theory that perceived usefulness, satisfaction, confirmation of expectations, and work-life balance all play a role in employees’ desire to continue telecommuting post-pandemic. Work-life balance was also found to be a significant mediator of the effect of expectation confirmation on job satisfaction. As a result, this research adds to the idea by including work-life balance literature to demonstrate that the behaviour of IT professionals is associated with their quality of work-life harmony. This study can assist businesses that plan to transition to hybrid work environments. With the needs of the emerging workplace still being uncharted territory for everyone, hybrid work models can be built and customized based on the findings of this study. This is imperative to fit the needs of employees and help organisations sustain their businesses.